2022
DOI: 10.1111/all.15432
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab significantly improves skin barrier function in patients with moderate‐to‐severe atopic dermatitis

Abstract: Background Atopic dermatitis (AD) is characterized by abnormal skin lipids that are largely driven by hyperactivated type 2 immune responses. The antibody to the α‐subunit of interleukin (IL)‐4 receptor, dupilumab, was recently approved to treat AD and demonstrated strong efficacy. However, the role of dupilumab therapy in the regulation of skin barrier structure and function has not been fully explored. Methods We have evaluated the content of lipids and transepidermal water loss (TEWL) in lesional and non‐le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 38 publications
9
52
0
2
Order By: Relevance
“…16 Multiple studies have shown that dupilumab treatment leads to clinical improvements 17 along with reductions of inflammatory cell infiltrates and proinflammatory cytokine and chemokine expression in lesions 18 and an enhanced skin barrier function with decreased transepidermal water loss (TEWL) and normalized epidermal lipid composition. [19][20][21][22][23][24] Likewise, an increased microbial diversity and decrease of S. aureus abundance during dupilumab treatment was reported. 25 Moreover, clinical signs of skin infections (mostly caused by S. aureus) were less frequent in dupilumab treated patients as compared to controls in prospective placebo-controlled studies.…”
Section: Introductionmentioning
confidence: 89%
“…16 Multiple studies have shown that dupilumab treatment leads to clinical improvements 17 along with reductions of inflammatory cell infiltrates and proinflammatory cytokine and chemokine expression in lesions 18 and an enhanced skin barrier function with decreased transepidermal water loss (TEWL) and normalized epidermal lipid composition. [19][20][21][22][23][24] Likewise, an increased microbial diversity and decrease of S. aureus abundance during dupilumab treatment was reported. 25 Moreover, clinical signs of skin infections (mostly caused by S. aureus) were less frequent in dupilumab treated patients as compared to controls in prospective placebo-controlled studies.…”
Section: Introductionmentioning
confidence: 89%
“…JAK/STAT pathway regulates the major signaling cascades for many cytokines, chemokines and growth factors, and it also participates in intracellular signal transduction and expression [ 21 ]. As shown in Figure 5 A,B, when cells were co-treated with TNF-α and IFN-γ, compound 1 significantly downregulated the phosphorylation of JAK2 and STAT3.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 Dupilumab treatment of patients with AD resulted in restoration of skin barrier function by restoring skin lipid composition subsequently decreasing transepidermal water loss. 25,26 The rapid ability of dupilumab to improve sense of smell was investigated further in a transgenic mouse model with IL-13 specifically expressed within the olfactory epithelium. 27 Neuronal loss was seen associated with inflammatory infiltration by macrophages and increased expression of a mucin gene, MUC5AC, and eosinophil chemokines although eosinophil levels were unexpectedly low.…”
Section: Dupilumab Efficacy Across Type 2 Inflammation and Restoratio...mentioning
confidence: 99%
“…23,24 Dupilumab treatment of patients with AD resulted in restoration of skin barrier function by restoring skin lipid composition subsequently decreasing transepidermal water loss. 25,26…”
Section: Dupilumab Efficacy Across Type 2 Inflammation and Restoratio...mentioning
confidence: 99%